The regional heterogeneity of wind power deployment: an empirical investigation of land-use policies in Germany and Sweden. Issue 4 (20th March 2020) - Lauf, Thomas; Ek, Kristina; Gawel, Erik; Lehmann, Paul; Söderholm, Patrik
Abstract : The purpose of this paper is to analyze and compare the impacts of land-use policies on wind power deployment at the regional levels in Germany and Sweden. We use data for the period 2008–2012, and an econometric approach in which the probability of having any wind power capacity additions and the actual level of increased capacity, given that it is positive, are permitted to be determined by different processes. The results confirm the importance of land-use policies, e.g., priority and exclusion areas, and interesting differences across the two countries are found. The impact of priority areas has been more profound in Germany, while the assignment of protected areas instead has constituted a more binding policy tool in Sweden. Cross-country differences in the relevance of various explanatory variables are linked to factors such as geographical patterns, design of wind power support schemes, and the allocation of decision-making power in planning processes.